2016
DOI: 10.21013/jmss.v3.n3.p16
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Maturity and Loneliness as Correlates of Life Satisfaction among Adolescents

Abstract: <p><em>Emotions which are considered as a basic factor of all relationships 1are very powerful and to a very great extent they control our behaviour, thoughts and all other aspects of life. The behaviour and thought processes are directly influenced by the past experiences and early developmental stages. Emotion is the feeling aspect of consciousness characterized by a physical aspect like physical arousal, behaviours that reveal emotion to the outside world, and an inner awareness of feelings.  He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…In line with this study, other studies have come to similar conclusions (24). Unlike the results of the present study that showed a lower emotional maturity on women in comparison to men, results in other studies conducted showed that gender had no effect on the level of emotional maturity on youths and adults (25), while a study indicated that emotional maturity in adolescent girls and female university students are more developed in comparison to their male counterparts (23).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with this study, other studies have come to similar conclusions (24). Unlike the results of the present study that showed a lower emotional maturity on women in comparison to men, results in other studies conducted showed that gender had no effect on the level of emotional maturity on youths and adults (25), while a study indicated that emotional maturity in adolescent girls and female university students are more developed in comparison to their male counterparts (23).…”
Section: Discussionsupporting
confidence: 88%
“…A study was conducted regarding emotional maturity on students showed that students were very unstable in terms of emotional maturity (22). Owing to the impact of emotional maturity on marital satisfaction (11) and satisfaction in life (23), it is necessary that adolescents, parents, educational administrators, and counselors should be more sensitive with regards to emotional maturity (5).…”
Section: Discussionmentioning
confidence: 99%
“…The results also show that the second hypothesis of the study showed that feeling lonely in relation to fear of negative evaluation has a mediating effect on psychological well-being, which is the research of Gollwitzer et al (2018), Momeni et al (2016 The lengths of social relationships and social anxiety were shown to be consistent and also with the researches of Wang, Mann, Lloyd-Evans, Ma, Johnson (2018), Johns et al (2016, Gandaharizadeh et al (2018), Setayeshi et al (2018). , Jenaabadi et al (2017) and Shaheen et al (2014) that the relationship of loneliness with social skills and mental well-being Cognitive behavior is also consistent with research by Maričić, Štambuk (2015) who demonstrated the mediating role of loneliness in the relationship between social anxiety and subjective well-being.…”
Section: Discussionsupporting
confidence: 67%
“…Defined (Borawski, 2018). Social skills-based research indicates that there is a relationship between feeling lonely and overly self-centered, lacking in respect for other people, being unacceptable to friends, which is more prevalent among female subjects (Johns, Mathew & Mathai, 2016). Loneliness can be a strong predictor of health and quality of life (Beutel et al, 2017) and may be associated with internal despair, poor social support, limited social networking, interpersonal skills shortages, and frequent psychiatric hospitalizations (Chrostek, Grygiel, Anczewska, Wciórka, Świtaj, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study found that there is a significant negative relationship between mental wellbeing and emotional immaturity. Thus, greater the emotional immaturity, lower will be the mental wellbeing as well as life satisfaction (Johns et al, 2016). Research suggests a positive correlation between emotional maturity and mental wellbeing, and a negative correlation between emotional immaturity and mental wellbeing in adults (Chavda, 2018;Sekhukhune, 2008;Spindler et al, 2016).…”
mentioning
confidence: 99%